Efektifitas SUSCATIN dalam Membentuk Keluarga yang Sakinah Mawaddah Wa Rahmah - Muhammad Al Faruq (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2019)
Abstract Ministry of Religious initiatives to implement the program in accordance with the regulations issued by the Director-General of Islamic Community guidance of the Department of Religious candidates for the No. DJ. II/491 Year 2009. Therefore, the quality of a marriage is determined by the readiness and maturity of the two prospective spouses to meet the life of the household in order to form a harmonious family in accordance with the premarital ideals. The research uses Research and Development (R&D) methods by combining qualitative and quantitative research. Qualitative data is obtained through verbal and written interview results. The problems that occur in the community that the effectiveness of the prospective bride course has not walked fully well, with a variety of factors that inhibit, so that the bride who has not understood the whole material about the concept of family Sakinah that has been poured in the course process Bride brides. For that, the research seeks to uncover the implementation of the bride candidate course at the Office of Religious Affairs (KUA) of Papar District of Kediri, as well as how the prospective bride understanding the family concept of Sakinah.